Sumbangan Efektivitas Panjang Tungkai, Kekuatan Otot Lengan, dan Kelincahan Gerak Terhadap Kemampuan Dribel Bola Basket Pada Siswa Putra Kelas XI MAN 3 Kediri - Ammardika Z, Alfian; Nurrochmah, Siti (Universitas Hamzanwadi, 2025)
This study aims to analyze the level of effectiveness of limb length, arm muscle strength and movement agility contributing to basketball dribbling ability in male students of class XI MAN 3 Kediri. This study applies a non-experimental design with an explanatory approach, which aims to identify the level of relationship between the independent variable and the dependent variable. The data sampling technique used purposive systematic porpotional random sampling technique totaling 42 students. This study uses quantitative descriptive statistics. The results of the contribution of the effectiveness of limb length with dribbling amounted to 18.8%, the contribution of the effectiveness of arm muscle strength with dribbling ability amounted to 19.6%, and motion agility with dribbling ability amounted to 35.9%. (X1) provides effectiveness of 18.8%, (X2) provides effectiveness of 19.6%, and (X3) provides effectiveness of 35.9%. As for the relative contribution to the independent variable (X1) of 25.3%, (X2) of 26.4%, and (X3) of 48.3%. Simultaneously, the independent variable of leg length (X1), the independent variable of arm muscle strength (X2), and the independent variable of movement agility (X3) amounted to 74.3%. This means that the high and low dependent variables of basketball dribbling ability (Y) of 74.3% are determined by the independent variable limb length (X1), arm muscle strength (X2) and the independent variable of motion agility (X3).